Covid-19 Case Management in Isolation and Quarantine Centers: A Review of Patients and Suspected Patients’ Justification for Abandoning Centers - Akantege, Raymond; Rahayu, Agus; Furqon, Chaerul; Dirgantari, Puspodewi (Image : Jurnal Riset Manajemen, 2023)
This paper finds out the justification of COVID-19 patients and suspected patients’ abandonment of isolation and quarantine centres. In this paper, the authors sought to identify the justification for escaping from isolation centers, to inform and modify decision markers strategies. The questions the paper sought to answer were, has escape from isolation centers by COVID-19 patients happened only in Ghana, what could be the main reasons behind escaping across the world, and how will the knowledge of these reasons help transform management practice achieve the best cooperation from patients The research method was largely qualitative, adopting a deductive and archival research approach. However, a quantitative research technique was used in reporting counts of documents evaluated for the study including escapees from the centers.  In this paper, fifteen published news items, 35 articles, and 22 textbooks were reviewed. The research revealed that escape from isolation centers has happened world-over, while stigmatization stands as the main reason for escaping. In conclusion, patients in the centers should be respected, and receive counseling, and daily updates of information on the well-being of their families and themselves.